A Portrait of Jephthah’s Daughter: Finding the Female Gaze - Shipp, Caitlyn (Lumen et Vita, 2024)
Judges 11:29-40 is among the most disturbing texts in the Hebrew Bible. It conveys the gruesome story about Jephthah’s daughter who becomes the victim of her father’s vow to YHWH, sacrificing whoever greets him first in return for victory in battle. Many biblical scholars in their laudable attempts to recover her within Scripture’s patriarchal lens contextualize the world behind and within the text. However, scholars are restrained, relying on the narrator’s male gaze and decision to bind her nameless identity to her father. While Scripture’s male testimony remains critical to constructing her portrait, it does not need to be limited to it. In the story’s reception history, only nineteenth-century artists singly capture the woman herself, freeing her association with Jephthah on the canvas. Artists such as James Jacques Joseph Tissot’s Jephthah’s Daughter and Tom Roberts’ A Study of Jephthah’s Daughter imagine her reaction to the news of her impending death. While their depictions of Jephthah’s daughter attempt to distance her from the male gaze, the paintings evoke the viewer to embody Jephthah’s eyes. However, there remains an unexplored female gaze lingering in the background, the voices of the text’s silent women who stood behind Jephthah’s daughter. They danced with her, but they were not the first to greet him. From their gaze, one can begin to imaginatively construct the unnamed woman. In my portrait of Jephthah’s daughter titled, Elizabeth’s Gethsemane Moment, relies upon biblical scholarship as well as the insights extrapolated from Tissot and Roberts’ portraits to create the female gaze from the perspective of the women who stood behind her. This paper argues that imagining the female gaze reveals an empowering Christoformic woman who lays down her life in the place of the expendable.